Social ontology, sociocultures and inequality in the global south - Baumann, Benjamin; Bultmann, Daniel (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Challenging the assumption that that the capitalist transformation includes a radical break with the past, this edited volume traces how historically older forms of social inequality are transformed but persist in the present to shape the social structure of contemporary societies in the global South. Each society comprises an interpretation of itself - including the meaning of life, the concept of a human being and the notion of a collective. This volume studies the interpretation that various societies have of themselves. This interpretation is referred to as social ontology. All chapters of the edited volume focus on the relation between social ontology and structures of inequality. They argue that each society comprises several historical layers of social ontology that correspond to layers of inequality, which are referred to as sociocultures. Thereby, the volume explains why and how structures of inequality differ between contemporary collectives in the global South, even though all of them seem to have similar structures, institutions, and economies. The volume is aimed at academics, students and the interested public looking for a novel theorization of social inequality pertaining to collectives in the global South"--
OCLC-licensed vendor bibliographic record.
Keywords: Social sciences -- Philosophy; Ontology; Equality -- Developing countries; Developing countries -- Social conditions; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General